Growth, Foreign Direct Investment and the Environment: Evidence from Chinese Cities - Matthew A. Cole; Robert J.R. Elliott; Jing Zhang (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
In this paper we investigate the relationship between economic growth and industrial pollution emissions in China using data for 112 major cities between 2001 and 2004. Using disaggregated data we separate FDI inflows from Hong Kong, Macao and Taiwan from those of other foreign economies. We examine four industrial water pollution indicators (wastewater, chemical oxygen demand, hexavalent chromium compounds, and petroleum-like matter) and four industrial air pollution indicators (waste gas, sulphur dioxide, soot and dust). Our results suggest that most air and water emissions rise with increases in economic growth at current income levels. The share of total output produced by firms from Hong Kong, Macao and Taiwan has a positive effect on emissions although this effect is only significant for three industrial water pollution emissions. The share of total output produced by firms from other foreign economies can be beneficial, detrimental or neutral, depending on the pollutants considered.
Keywords: O13; O18; Q25; O53; R1; F23; 330; FDI; economic growth; pollution; cities